2002
DOI: 10.1245/aso.2002.9.1.27
|View full text |Cite
|
Sign up to set email alerts
|

The superiority of ratio-based lymph node staging in gastric carcinoma

Abstract: Ratio-based lymph node staging is simple and gives more precise information for prognosis with fewer problems related to stage migration than the 1997 UICC/AJCC staging system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
185
0
12

Year Published

2003
2003
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(208 citation statements)
references
References 27 publications
11
185
0
12
Order By: Relevance
“…To overcome these shortcomings of the TNM staging system, some authors suggested use of LNR, defined as the ratio of metastatic to total number of lymph nodes. In gastric cancer, ratio-based nodal staging was shown to be better than number-based classification in defining stage migration [12][13][14]20]. In addition ratiobased staging has been reported to significantly predict oncologic prognosis in patients with colon cancer [16,21].…”
Section: Discussionmentioning
confidence: 99%
“…To overcome these shortcomings of the TNM staging system, some authors suggested use of LNR, defined as the ratio of metastatic to total number of lymph nodes. In gastric cancer, ratio-based nodal staging was shown to be better than number-based classification in defining stage migration [12][13][14]20]. In addition ratiobased staging has been reported to significantly predict oncologic prognosis in patients with colon cancer [16,21].…”
Section: Discussionmentioning
confidence: 99%
“…Atualmente, além da importância do total de linfonodos dissecados, vem ganhando destaque o quociente linfonodos acometidos/ linfonodos dissecados 16 . Inicialmente, este parâmetro foi utilizado em trabalhos de câncer gástrico, em que se verificou que o quociente linfonodal era fator independente de sobrevida 19,20 .…”
Section: Discussionunclassified
“…The incorporation of both the number of PLNs and the number of negative lymph nodes (and, thus, the TLNs assessed) to calculate the LNR provided further prognostic power, a finding that is similar to reports from studies in breast cancer, gastric cancer, and colon cancer. [27][28][29] However, as with studies in those other sites, the best use of the LNR in clinical decision-making remains unclear.…”
Section: Lymph Nodes In Small Bowel Carcinoma/overman Et Almentioning
confidence: 99%